Clinical and Economic Consequences of Vancomycin and Fidaxomicin for the Treatment of Clostridium difficile Infection in Canada. Issue 2 (2014) - Wagner, Monika; Lavoie, Louis; Goetghebeur, Mireille
Abstract : BACKGROUND: Clostridium difficile infection (CDI) represents a public health problem with increasing incidence and severity. OBJECTIVE: To evaluate the clinical and economic consequences of vancomycin compared with fidaxomicin in the treatment of CDI from the Canadian health care system perspective. METHODS: A decision-tree model was developed to compare vancomycin and fidaxomicin for the treatment of severe CDI. The model assumed identical initial cure rates and included first recurrent episodes of CDI (base case). Treatment of patients presenting with recurrent CDI was examined as an alternative analysis. Costs included were for study medication, physician services and hospitalization. Cost effectiveness was measured as incremental cost per recurrence avoided. Sensitivity analyses of key input parameters were performed. RESULTS: In a cohort of 1000 patients with an initial episode of severe CDI, treatment with fidaxomicin led to 137 fewer recurrences at an incremental cost of 1.81 million, resulting in an incremental cost of 13, 202 per recurrence avoided. Among 1000 patients with recurrent CDI, 113 second recurrences were avoided at an incremental cost of 18, 190 per second recurrence avoided. Incremental costs per recurrence avoided increased with increasing proportion of cases caused by the NAP1/B1/027 strain. Results were sensitive to variations in recurrence rates and treatment duration but were robust to variations in other parameters. CONCLUSIONS: The use of fidaxomicin is associated with a cost increase for the Canadian health care system. Clinical benefits of fidaxomicin compared with vancomycin depend on the proportion of cases caused by the NAP1/B1/027 strain in patients with severe CDI.